Thoracic Endovascular Aortic Repair for Type B Acute Aortic Dissection Complicated by Descending Thoracic Aneurysm. (June 2017) - Piffaretti, G.; Ottavi, P.; Lomazzi, C.; Franchin, M.; Micheli, R.; Ferilli, F.; Dorigo, W.; Marrocco-Trischitta, M.; Castelli, P.; Trimarchi, S.
Abstract : Objectives: To analyse the results and review the literature about thoracic aortic endovascular repair (TEVAR) for type B acute aortic dissection (TBAAD) complicated by descending thoracic aortic aneurysm (DTA) in the hyperacute or acute phases. Methods: This was a multicentre, observational descriptive study. Inclusion criteria were TBAAD with a DTA of ≥50 mm, TBAAD on an already known aneurysmal descending thoracic aorta, and TBAAD presenting with an enlarged aorta with a total diameter <50 mm, but with >50% diameter increase compared with a previous computed tomography angiography (CTA) showing a non-dissected aorta with normal sizing. Primary endpoints were early and long-term survival, freedom from TEVAR and aortic related mortality (ARM), and freedom from re-intervention. Results: Twenty-two patients were included in the analysis. The mean aortic diameter was 66 ± 26 mm (range 42–130; IQR 51–64). The in hospital TEVAR related mortality was 14% ( n = 3). The mean radiological follow-up was 56 ± 45 months (range 6–149; IQR 12–82), and the follow-up index 0.97 ± 0.1. All surviving patients were available for follow-up. During follow-up the cumulative mortality was 26% ( n = 5) and TEVAR related mortality was 5% (n = 1). Overall the estimate of survival was 82% (95%CI: 61.5–93) at 1 year, and 64% at 5 years. Ongoing primary clinical success was 79% (re-intervention n = 4). Freedom from aortic related mortality was 86% (95%CI: 66–95) at 1 and 5 year, while freedom from re-intervention was 95% (95%CI: 75.5–95) at 1 year, and 77% (95%CI: 50–92) at 5 years. Conclusions: In our experience, DTA is a frequent complication from the very beginning of the clinical onset of TBAAD. In this high-risk cohort, TEVAR showed satisfactory results, better than those predicted by the risk score for open repair, with favourable stability of the aortic diameter and no aortic related adverse events during follow-up.